Torus Harmonic Analysis and Prediction of Global Ionospheric TEC - FENG Wei; ZHANG Chuanding; WU Xing; WANG Kai (Surveying and Mapping Press, 2018)
It is established that an Ionospheric TEC spherical harmonic model based on torus harmonic analysis, by applying the torus harmonic analysis method which is ripe in gravity research into modeling Ionospheric TEC. The characteristics of the proposed model parameters are tested and analyzed in detail. The results show that the proposed model fitting accuracy is excellent. When coefficients truncated to 15th order, the recovery error is less than 4% all the year. The spherical harmonic model has good applicability except the Arctic and the Antarctic area. The characteristics of the proposed spherical harmonic model coefficients is estimated. It is applied that the degree-by-degree residual modeling method, and approaches the regularity of the spherical harmonic coefficients with the use of trend function, power spectrum analysis theory and the ARMA model. The rules of the proposed model coefficient changes are discovered, and then the prediction model is established. Therefore, the prediction based on the model coefficients is achieved. Besides, the accuracy variation problem of prediction coefficients and the data accumulation time of coefficients short-term prediction are analyzed. Finally through the prediction of TEC, the precision of this model is verified.